2020
DOI: 10.1177/1087054720959712
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Dynamic Community Structure of Patients with Attention-Deficit/Hyperactivity Disorder in the Resting State

Abstract: Objective: Some static network studies have suggested that the community structure in the brains of ADHD patients is altered. However, ADHD is now increasingly regarded as a disorder of neural dynamics, but the dynamic reconstruction of brain communities in ADHD patients is far from being understood. Method: Forty-two ADHD patients and fifty healthy controls participated in this study. We constructed a multilayer network model and calculated several metrics for quantifying community reconstruction at different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 59 publications
0
11
2
Order By: Relevance
“…Meanwhile, hyperconnectivity patterns were also widely reported in ADHD subjects [30,58,59], which would potentially "lock" regions together, constrain regional module transition frequency, and reduce neural flexibility. Nevertheless, recent adult studies using the multilayer framework reported that adults with ADHD had higher flexibility and lower integration coefficient than of control subjects [60,61], opposite to our findings. While several potential factors may explain the observed discrepancies, one of the most plausible reasons may be the difference in age across the studies (current cohort: mean age 11.65 years; adult cohorts: mean age 32 years).…”
Section: Discussioncontrasting
confidence: 99%
“…Meanwhile, hyperconnectivity patterns were also widely reported in ADHD subjects [30,58,59], which would potentially "lock" regions together, constrain regional module transition frequency, and reduce neural flexibility. Nevertheless, recent adult studies using the multilayer framework reported that adults with ADHD had higher flexibility and lower integration coefficient than of control subjects [60,61], opposite to our findings. While several potential factors may explain the observed discrepancies, one of the most plausible reasons may be the difference in age across the studies (current cohort: mean age 11.65 years; adult cohorts: mean age 32 years).…”
Section: Discussioncontrasting
confidence: 99%
“…The element gives the connection strength from node of layer to node of layer , which is called “inter-layer coupling parameter”. Here, we set the structure resolution parameter and the inter-layer coupling parameter to the default value of 1 [ 8 , 26 , 27 ].…”
Section: Methodsmentioning
confidence: 99%
“…Intuitively, structural boundary controllability measures the necessary input required by a node to drive the overall system along a desired trajectory (Gu, Pasqualetti, et al, 2015). The role of controllability in regulating dynamic brain state transitions as well as predicting the maturity of adolescent brain systems during development has been corroborated by several recent studies (Cornblath et al, 2020;Cui et al, 2020;Tang et al, 2017).…”
Section: Introductionmentioning
confidence: 79%